Chronic TrkB agonist treatment in old age does not mitigate diaphragm neuromuscular dysfunction. Issue 1 (13th January 2017) - Greising, Sarah M.; Vasdev, Amrit K.; Zhan, Wen‐Zhi; Sieck, Gary C.; Mantilla, Carlos B.
Abstract: Previously, we found that brain‐derived neurotrophic factor (BDNF) signaling through the high‐affinity tropomyosin‐related kinase receptor subtype B (TrkB) enhances neuromuscular transmission in the diaphragm muscle. However, there is an age‐related loss of this effect of BDNF/TrkB signaling that may contribute to diaphragm muscle sarcopenia (atrophy and force loss). We hypothesized that chronic treatment with 7, 8‐dihydroxyflavone (7, 8‐DHF), a small molecule BDNF analog and TrkB agonist, will mitigate age‐related diaphragm neuromuscular transmission failure and sarcopenia in old mice. Adult male Trk B F 616A mice ( n  = 32) were randomized to the following 6‐month treatment groups: vehicle‐control, 7, 8‐DHF, and 7, 8‐DHF and 1NMPP1 (an inhibitor of TrkB kinase activity in Trk B F 616A mice) cotreatment, beginning at 18 months of age. At 24 months of age, diaphragm neuromuscular transmission failure, muscle‐specific force, and fiber cross‐sectional areas were compared across treatment groups. The results did not support our hypothesis in that chronic 7, 8‐DHF treatment did not improve diaphragm neuromuscular transmission or mitigate diaphragm muscle sarcopenia. Taken together, these results do not exclude a role for BDNF/TrkB signaling in aging‐related changes in the diaphragm muscle, but they do not support the use of 7, 8‐DHF as a therapeutic agent to mitigate age‐related neuromuscular dysfunction. Abstract : Our study investigated chronic 7, 8‐DHF (highly selective BDNF analog and TrkB agonist) treatment as a mitigating agent for age‐related diaphragm neuromuscular transmission failure and sarcopenia (atrophy and force loss). While the results did not support chronic 7, 8‐DHF treatment as an effective therapeutic agent, they do not exclude a role for BDNF/TrkB signaling in aging‐related changes in the diaphragm muscle.